Filosofiniai Senekos raštai: humanizmo pamokos? - Aleknienė, Tatjana (Literatūra, 2015)
Seneca’s name is often associated with the notion of „humanism“. In this article we attempt to verify and define the meaning of this notion in the context of Seneca’s writings. Our question is: what kind of philosophy, according to Seneca, can be useful and delivering to a man afflicted with life’s many misfortunes? This question encompasses all the main meanings of both Latin humanitas and later European “humanism”, because it concerns “humanities” (humanitas as paide%a), which best of all suites the true human nature (humanitas as the true essence of human being); we also ask: what should philosophic education be so that it helps the struggling humankind (humanitas as filanqrwp%a). Such an amalgam of ideas is not our construct, but is actually found in the writings by Seneca himself. However, in this way following Seneca’s thought, we discover rather paradoxical species of “humanism”, the one which should be called “cosmo-centrism”.